Економічна ефективність підприємств хлібобулочних галузей - Шеянова, Еліна Дмитрівна (НТУ "ХПІ", 2018)
Стаття присвячена аналізу економічної ефективності на підприємствах хлібобулочних галузей. У статті досліджено та узагальнено теоретичні підходи до визначення сутності ефективності діяльності підприємств. Економічна ефективність – досягнення найбільших результатів за найменших витрат праці. Економічна ефективність – конкретна форма вияву закону економії часу, їх зв'язок здійснюється через зростання продуктивності праці, її підвищення означає зростання ефективності сукупної праці, збільшення ефективності всього виробництва, зумовленої насамперед прогресом продуктивних сил.

The article is devoted to the analysis of economic efficiency of bakery branches. Investigates and generalises theoretical approaches to the definition of the essence of the efficiency of enterprises. Economic efficiency – achieving the greatest results with the least labor costs. Economic efficiency is a concrete form of the manifestation of the law of saving time, their connection is effected through the growth of labor productivity. Its increase means an increase in the efficiency of aggregate labor, an increase in the efficiency of all production, primarily due to the progress of the productive forces. Economic efficiency is a complex category of economic science. It permeates all spheres of human practice, all stages of social production, is the basis for constructing quantitative criteria for the value of the decisions made, is used to form the material, structural, functional and systemic characteristics of economic activity. One can say that the most essential characteristics of economic activity, such as integrity, multilateralism, dynamism, multidimensionality and interconnectedness of its various parties, are adequately reflected through the category of efficiency.The analysis of the overall efficiency of economic activity is the prerogative of the highest level of management structures of the organization. The effectiveness or ineffectiveness of private management decisions related to product price determination, the size of the batch of procurement or supply of products, the replacement of equipment or technology and other solutions should be evaluated in terms of overall success of the firm, the nature of its economic growth and the growth of overall efficiency.
Economic efficiency of bakery branch companies
Keywords: результативність; раціональне використання; управління; економічні відносини; рішення; переваги; сутність; efficiency; effectiveness; rational use; management; relations; solutions; advantages; essence